Optimization of growth conditions and oil extraction from microalgae. - Leow, Daniel Chee Hui. (2010)
Microalgae are a diverse range of eukaryotic or prokaryotic microscopic organisms. The increasing interest in microalgae as a source of renewable lipids for biodiesel production has led to more intense identification of new and suitable species of microalgae for the above mentioned aim. Given the simplicity of their cellular structure and the fact that they can produce their own food by heterotrophic or autotrophic pathways, they have the ability to propagate rapidly and achieve a massive amount of biomass in a short period of time. Under certain nutrient-limiting conditions, lipid production picked up rapidly, thus laying the foundation for lipid extraction from a lipid-rich source for bio-diesel production. Some of the nutrient limiting conditions includes light-limitation and nitrogen limitation. However nitrogen limitation may have an adverse effect on the biomass production and thus negatively impacts the quantity of lipids produced. Therefore, these factors must be carefully optimized. Genetic modification of the microalgae such as in limiting production of chlorophyll molecules also has a positive effect on the production of lipids. Certain growth and extraction methods suggested by other authors will be further discussed and analyzed to achieve the overall economy of scale. This paper seeks to identify a few key factors for economical agriculture of microalgae and lipid extraction as well as identifying certain promising microalgae for the production of biofuel. This paper also contains a few suggestive experiments which could improve the production and extraction of biodiesel from the microalgae and the postulated results will be discussed.